Defining brain health: A concept analysis. (14th May 2021) - Chen, Yaohua; Demnitz, Naiara; Yamamoto, Stacey; Yaffe, Kristine; Lawlor, Brian; Leroi, Iracema
Abstract: Objectives: Brain health is an important focus for coming decades due to population ageing. Although the term 'brain health' is increasingly used in lay and professional settings, a clear definition of the term is lacking. We conducted an analysis of the concept of brain health to inform policy, practice, and research. Methods: We applied a hybrid concept analysis method involving three stages: (1) a review of the extant literature for definitions of brain health; (2) field work, involving an international survey of 'brain health' researchers and practitioners; and (3) a final analysis, integrating the findings into a working definition and model. Results: Our review of the literature identified 13 articles defining brain health, six of which proposed their own definition. Our survey revealed that the term 'brain health' was used in diverse ways based on different theoretical frameworks. From the review and survey, we extracted attributes, antecedents, and consequences of brain health. These were synthesized into a definition of brain health as a life‐long, multidimensional, dynamic state consisting of cognitive, emotional and motor domains underpinned by physiological processes and can be objectively measured and subjectively experienced. It is influenced by eco‐biopsychosocial determinants. Conclusion: This working definition of brain health is a foundation for developing policy, practice, research and advocacy. The definition needs to be operationalised through further development of empirical referents, including cross‐cultural understanding, adaptation and validation. Key Points: Brain health can be defined as a multidimensional, dynamic state, occurring along the life course, and incorporating cognitive, emotional, and motor domains underpinned by physiological processes Brain health can be objectively measured and subjectively experienced Brain health is influenced by eco‐biopsychosocial determinants, resulting in a continuum of quality of life and wellness Our definition opens the possibility of embracing positive outcomes, regardless of the starting point on the continuum of brain health